From frailty to resilience: exploring adaptive capacity and reserve in older adults–a narrative review - Cosarderelioglu, Caglar; Walston, Jeremy D.; Abadir, Peter M. (Frontiers in Aging, 2025)
Resilience, the capacity to adapt and recover from adversity, plays a critical role in the health and wellbeing of older adults. In geriatric populations, resilience encompasses physical, cognitive, and psychosocial domains and is essential for maintaining functional independence and quality of life amidst the challenges of aging. This review explores the concept of resilience within geriatric medicine across physical, cognitive, and psychosocial domains, highlights the differences from frailty and reserve, underscores importance of stressors, summarizes key biomarkers that predict resilience, and evaluates interventions designed to enhance resilience in older adults.